Factors Affecting the Rupiah Exchange Rate During the Covid 19 Pandemic - Chasanah, Amalia Nur; Riyono, Riyono; Ristanto, Hesti (Global Health Science Group, 2022)
The world economy throughout 2020 experienced a shock due to the Covid 19 virus pandemic. Indonesia was no exception, it also experienced economic instability. As a country that is rich in raw materials, it still relies heavily on raw materials from abroad. Thus, the volatility of the exchange rate becomes a major influence on the production process in various fields. This study aims to determine the effect of inflation, interest rates and the money supply on the exchange rate before and during the Covid 19 pandemic. The data used are exchange rates, interest rates, inflation and the money supply from January 2018 to April 2021. Where the period is divided into the period before the Covid pandemic occurred, namely January 2018 to February 2020 and during the pandemic from March 2020 to April 2021. The data analysis technique used was multiple regression with the classical assumptions of multicollinearity, autocorrelation, heteroscedasticity and normality. The results showed that the inflation variable, interest rate and the dummy variable had a positive and significant effect on the exchange rate, while the money supply had no significant negative effect on the exchange rate. The adjusted r square value is 0.565 which means that the inflation variable, interest rate, money supply and the dummy variable are able to explain the exchange rate of 56.5% while the rest is explained by other variables not included in this study.